Hypergolic Triggers as Co‐crystal Formers: Co‐crystallization for Creating New Hypergolic Materials with Tunable Energy Content. Issue 51 (6th November 2019) - Titi, Hatem M.; Arhangelskis, Mihails; Rachiero, Giovanni P.; Friščić, Tomislav; Rogers, Robin D.
Abstract: We demonstrate a co‐crystal‐based strategy to create new solid hypergols, that is, materials exhibiting spontaneous ignition when in contact with an oxidant, from typically non‐hypergolic fuel molecules. In these materials, the energy content and density can be changed without affecting the ignition delay. The use of an imidazole‐substituted decaborane as a hypergolic "trigger" component in combination with energy‐rich but non‐hypergolic nitrobenzene or pyrazine yielded hypergolic co‐crystals that combine improved combustion properties with ultrashort ignition delays as low as 1 ms. Abstract : It′s not rocket science : Co‐crystallization of a hypergolic decaborane building block designed for hydrogen bonding with energetic but not hypergolic or explosive fuel molecules enables the simple and rapid synthesis of new hypergolic materials with tunable energetic properties and ultrashort ignition delays down to 1 ms.